Prospective Longitudinal Characterization of the Relationship between Diabetes and Cardiac Structural and Functional Changes. (8th February 2022) - Chowdhary, Amrit; Jex, Nicholas; Thirunavukarasu, Sharmaine; MacCannell, Amanda; Haywood, Natalie; Almutairi, Altaf; Athithan, Lavanya; Jain, Manali; Craven, Thomas; Das, Arka; Sharrack, Noor; Saunderson, Christopher E. D.; et al.
Abstract : Objectives . In a cohort of type 2 diabetic (T2D) patients who underwent baseline cardiac magnetic resonance (CMR) and biomarker testing, during a median follow-up of 6 years, we aimed to determine longitudinal changes in the phenotypic expression of heart disease in diabetes, report clinical outcomes, and compare baseline clinical characteristics and CMR findings of patients who experienced major adverse cardiovascular events (MACE) to those remaining MACE free. Background . T2D increases the risk of heart failure (HF) and cardiovascular mortality. The long-term impact of T2D on cardiac phenotype in the absence of cardiovascular disease and other clinical events is unknown. Methods . Patients with T2D ( n = 100) with no history of cardiovascular disease or hypertension were recruited at baseline. Biventricular volumes, function, and myocardial extracellular volume fraction (ECV) were assessed by CMR, and blood biomarkers were taken. Follow-up CMR was repeated in those without interim clinical events after 6 years. Results . Follow-up was successful in 83 participants. Of those, 29 experienced cardiovascular/clinical events (36%). Of the remaining 59, 32 patients who experienced no events received follow-up CMR. In this cohort, despite no significant changes in blood pressure, weight, or glycated hemoglobin, significant reductions in biventricular end-diastolic volumes and ejection fractions occurred over time. The mean ECV was unchanged. Baseline plasma high-sensitivity cardiac troponin T (hs-cTnT) was significantly associated with a change in left ventricular (LV) ejection fraction. Patients who experienced MACE had higher LV mass and greater LV concentricity than those who remained event free. Conclusions . T2D results in reductions in biventricular size and systolic function over time even in the absence of cardiovascular/clinical events.